Grundtvigs brug af det islandske digt Odins ravnegalder - Lassen, Annette (Danske Studier, 2022)
The article investigates N.F.S. Grundtvig‘s reception of the Icelandic eddic poem Hrafnagaldur Óðins / Forspjallsljóð and is a contribution to knowledge about the nineteenth century reception of Old Icelandic literature in Denmark. In his writings from 1807 to 1860 Grundtvig repeatedly returned to, reevaluated, and reinterpreted Hrafnagaldur Óðins. In his puzzlement over the poem Grundtvig was not alone: Since the beginning of research scholars have struggled with this poem, and hypotheses about its age, importance, and significance have varied to a greater extent than is true of most other eddic poems. In the nineteenth century, Hrafnagaldur Óðins was considered to be one of the most important sources to Old Norse mythology, whereas today it is largely forgotten and has been dropped from collections of eddic poetry, because it is no longer dated to the Middle Ages but is believed to be written in the seventeenth century. In 1807, Grundtvig quoted a stanza of Hrafnagaldur Óðins as an emblem for the gloomy destiny of the Æsir; in 1832, he considered the poem a little symbolic tale about sunrise and sunset; in 1847, he read it as a cheerful comedy about immortality and marriage; and finally, in 1860, the poem inspired him to give expression to a Christian utopia in his Dansk Ravnegalder. Thus, his attitude and use of the poem changed substantially throughout his oeuvre, which gives testimony to Grundtvig’s zealous and tireless philological work.